2022
DOI: 10.3389/fmed.2022.950883
|View full text |Cite
|
Sign up to set email alerts
|

Switching from one biologic to benralizumab in patients with severe eosinophilic asthma: An ANANKE study post hoc analysis

Abstract: BackgroundSevere asthma is a heterogeneous inflammatory disease driven by eosinophilic inflammation in the majority of cases. Despite biologic therapy patients may still be sub-optimally controlled, and the choice of the best biologic is a matter of debate. Indeed, switching between biologics is common, but no official guidelines are available and real-world data are limited.Materials and methodsIn this post hoc analysis of the Italian, multi-center, observational, retrospective study, ANANKE. Patients with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…Demographic characteristics at index date were similar between naïve and bio-experienced patients, while clinical characteristics showed some differences between the two groups (Additional file 5 : Table S5). In agreement with the post hoc data reported by Caruso et al [ 24 ], naïve population had a shorter median duration of SEA (1.6 years naïve patients vs 3.5 years bio-experienced patients, IQR 1.0–3.0 vs 1.6–6.5, respectively), the bio-experienced group had a greater proportion of atopic patients (45.2% naïve patients vs 55.3% bio-experienced patients) and a higher frequency of OCS-related conditions (35.5% naïve patients vs 52.6% bio-experienced patients). Accordingly, OCS use appeared to be slightly higher in the bio-experienced group (24.2% naïve patients vs 28.9% bio-experienced patients) while BEC was slightly lower (median BEC: 605 cells/mm 3 IQR 440–915 in naïve patients vs 550 cells/mm 3 IQR 300–756 in bio-experienced patients).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Demographic characteristics at index date were similar between naïve and bio-experienced patients, while clinical characteristics showed some differences between the two groups (Additional file 5 : Table S5). In agreement with the post hoc data reported by Caruso et al [ 24 ], naïve population had a shorter median duration of SEA (1.6 years naïve patients vs 3.5 years bio-experienced patients, IQR 1.0–3.0 vs 1.6–6.5, respectively), the bio-experienced group had a greater proportion of atopic patients (45.2% naïve patients vs 55.3% bio-experienced patients) and a higher frequency of OCS-related conditions (35.5% naïve patients vs 52.6% bio-experienced patients). Accordingly, OCS use appeared to be slightly higher in the bio-experienced group (24.2% naïve patients vs 28.9% bio-experienced patients) while BEC was slightly lower (median BEC: 605 cells/mm 3 IQR 440–915 in naïve patients vs 550 cells/mm 3 IQR 300–756 in bio-experienced patients).…”
Section: Resultssupporting
confidence: 93%
“…Patients also experienced an overall improvement in lung function and asthma control, resulting in a decreased utilization of healthcare resources [ 22 ]. Additional post hoc analyses were carried out and revealed that benralizumab maintained its efficacy independently of presence of atopy, body mass index (BMI) [ 22 ], presence of nasal polyps [ 23 ], use of previous biologics [ 24 ] and BEC [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A new post hoc analysis has been conducted from the real-life ANANKE study, in which the clinical characteristics and outcomes in naïve and bio-experienced SEA patients treated with benralizumab were described for up to 96 weeks. The findings here support earlier research with a shorter treatment duration (median of 9.8 months) 36 and demonstrate the sustained response of benralizumab in patients characterized by an eosinophilic-driven SA phenotype which failed to respond to previous biologics. Novel data have also been generated by analyzing bio-experienced patients split into omalizumab and mepolizumab groups.…”
Section: Discussionsupporting
confidence: 90%
“…The long-term OCS dose reduction shown in this study exceeds the results previously communicated by Caruso et al, in which naïve and bio-experienced patients reached median daily OCS doses of 4.5 mg and 8.6 mg, respectively, after a median period of 9.8 months (reductions of 61.9% and 49.1%, respectively). 36 Indeed, at 48 and 96 weeks, naïve patients maintained a median OCS dose of 0 mg/daily, while bio-experienced patients had a slight increase in median OCS dose from 0 to 1.9 mg/daily. As already explained above, such a modest increment was not caused by an actual increase in OCS dosage but rather by the low number of bio-experienced patients, which further decreased at 96 weeks.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation